Dentist-related factors influencing the amount of prosthodontic treatment provided - Kronstro¨m M, Palmqvist S, So¨derfeldt B, Carlsson GE (Blackwell Synergy, 2000)
To evaluate, using multivariate methods, the associations between indicators of the amount of prosthodontic treatment and dentist-related factors. Methods: Questionnaires were sent to a random sample of 2059 general dentists, response rate was 76%. Two indicators of prosthodontic activity were used as dependent variables: 1) reported weekly working hours used for prosthodontics and 2) reported numbers of produced single crowns, fixed partial dentures, and removable dentures. Independent variables were ‘social and demographic attributes’, ‘job situation’ and ‘attitudes of dentists’.